A novel Pt/pyridine ionic liquid polyoxometalate/rGO tri-component hybrid and its enhanced activities for methanol electrooxidation. (20th January 2019) - Shi, Hongli; Wang, Ruiying; Lou, Mengran; Jia, Dianzeng; Guo, Yong; Wang, Xingchao; Huang, Yudai; Sun, Zhipeng; Wang, Tao; Wang, Luxiang
Abstract: A novel tri-component hybrid, Pt/pyridine ionic liquid polyoxometalate/reduced graphene oxide denoted as Pt/(epy)3 PMo12 O40 /rGO with well-dispersed, smaller size Pt nanoparticles on rGO is successfully synthesized. The morphology, structure, composition and electrochemical property are characterized by high resolution transmission electron microscopy, X-ray diffraction, X-ray photoelectron spectroscopy, energy dispersive spectrometer, Raman spectra, thermogravimetric analysis and cyclic voltammetry, respectively. Ionic liquid polyoxometalate (epy)3 PMo12 O40 availably prevents the aggregations of Pt nanoparticles on the rGO surface, furthermore, effectively improves anti CO poisoning performance and enhances the conductivity of the material. The mass activity of as-prepared Pt/(epy)3 PMo12 O40 /rGO catalyst for methanol oxidation is about 10 times of 20% commercial platinum carbon, 7 times of Pt/rGO, 4 times of Pt/epyBr/rGO, and 2 times of Pt/H3 PMo12 O40 /rGO. This further demonstrates that the ionic liquid polyoxometalate (epy)3 PMo12 O40 play a very important role in enhancing the eletrocatalytic activity of the tri-component hybrid composite catalyst. Graphical abstract: Highlights: A novel Pt/(epy)3 PMo12 O40 /rGO tri-component hybrid is fabricated. The Pt/(epy)3 PMo12 /rGO exhibits enhanced methanol electrooxidation activity. The Pt/(epy)3 PMo12 /rGO catalyst has the outstanding anti CO poisoning performance. It is worth looking forward to using such an excellent catalyst in anode catalysts of DMFC.